Particles ‘halt’ and ‘eben’ in German: Functions, Combinatorial Compatibility, and Syntactic Properties - A. V. Averina; E. L. Shubina (Научный диалог)
This study analyzes the similarities and distinctive features of the German particles ‘halt’ and ‘eben’. It examines their combinatorial compatibility, functional roles, and syntactic usage. The relevance of this research is underscored by the need for further exploration of the potential use of the particles ‘halt’ and ‘eben’ in illocutionarily dependent subordinate clauses, as well as the types of modal meanings they convey. Through descriptive, transformational, comparative, and contextual analysis methods, it is demonstrated that ‘halt’ and ‘eben’ differ from other modal particles in that they indicate the factuality of a situation. A specific characteristic of the particle ‘halt’ is its ability to introduce additional emotive meanings into an utterance, making it prevalent in colloquial speech. It is noted that ‘eben’ serves as an indicator of inferential evidentiality. The analysis of the compatibility of these particles with modal words reveals that ‘halt’ and ‘eben’ are incompatible with markers of reportative evidentiality. Investigating various uses of ‘halt’ and ‘eben’ in subordinate clauses allows for the observation that their compatibility with illocutionarily dependent clauses can be attributed to their function in affirming the truth of a proposition.